(untitled) (Journal of Contemporary Studies, 2025)
Both United States of America and China have their unique strategic narratives in the Asia Pacific guided by their respective political history. This distinction hampers regional cooperation in the region and compels the world powers to opt for the zero-sum game. The US aims to fill the power vacuum in the region by adopting anti-China policies through alliances build-up, while China seeks to counter American presence through trade and connectivity. One of the major US partners in the Asia Pacific is Australia, which is taken as a case study because it openly advocates for profound political and strategic engagement with the US and has lately garnered world attention through the controversial AUKUS deal. The US perspective receives China’s actions in the South China Sea as assertive and its economic and military policies as efforts to reshape regional norms and institutions to serve its strategic interests. By challenging the established order that has fostered stability, China is portrayed as a revisionist power threatening the foundations of the current international system. In response, China’s strategic narrative is aimed to project its capacity to shape the international order, economically uplift and link regions through its Belt and Road Initiative (BRI) using soft power and maintaining its influence in the Asia-Pacific region. This duality of narratives underscores the escalating geopolitical tensions and a struggle for dominance and influence in shaping the future of the Asia-Pacific region.